2017
DOI: 10.3390/fermentation3030045
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Production of the Bioactive Peptides Endolides A and B and the Polyketide Mariline A from the Sponge-Derived Fungus Stachylidium bicolor 293K04

Abstract: Previous investigations of the sponge-derived fungus Stachylidium bicolor (S. bicolor)293K04 led to the isolation of the biosynthetically unusual polyketides marilines A-C and the bioactive tetrapeptides endolides A-B, identified as potential neuropathic drug leads. Furthermore, prior extended solid cultivation of S. bicolor 293K04 for 60 days resulted in a significant increase of polyketide yield, and the isolation of seven new polyketides. Due to the interest in endolide activity, unusual biosynthetic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…2) in solid and liquid media following cultivation periods of ca. 40 days (17,25). Here, we isolated from the culture extracts of S. bicolor also the new natural product onychocin D (see details in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) in solid and liquid media following cultivation periods of ca. 40 days (17,25). Here, we isolated from the culture extracts of S. bicolor also the new natural product onychocin D (see details in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Culture media were BMS (biomalt with added artificial seawater: Villa Natura Kraftnahr biomalt, 20 g/liter; sea salts [Sigma], 40 g/liter), TSB (Trypticase soy broth; BD, Difco), or oatmeal (BD, Difco). Fungal cultures on liquid media (10 ml, EPA vials) were performed as previously described (25). Conidia from 25-day-old cultures grown on solid oatmeal were gently harvested with a loop using a saline (0.8% NaCl) solution containing 0.0025% Tween 80.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 7 days, the zones were constant on E. coli (ATCC 25922) and there was insignificant decrease at day 8 and 9 on S. aureus (ATCC 25925). The decrease might be due to autolysis that might have occurred as the nutrients depleted [43]. In addition, at day 7, the inhibitive intensity of the secondary metabolites in the broth implied that the fungus produced active antibacterial metabolites optimally at its stationary phase.…”
Section: Secondary Metabolite Production Stagementioning
confidence: 99%
“…To further filter for endolide analogs that are supposedly produced in sufficient amounts for isolation and structure elucidation, only nodes with an intensity (sum of precursor ion) greater than 1.5 × 10 6 were retained, as it was shown before that the peak areas of [M + H] + adducts and concentrations of endolides correlate well. 32 Previous yields of 24.6 mg/L after reisolation of the known endolide A (Table S3, Figure S3) indicated that nodes below this threshold would have yields below 0.1 mg/10L. In this way, we generated a MassQL-annotated molecular network with substructural information for all endolides.…”
mentioning
confidence: 99%